2021
DOI: 10.1021/acsptsci.0c00189
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 2A Receptor (5-HT2AR) Activation by 25H-NBOMe Positional Isomers: In Vitro Functional Evaluation and Molecular Docking

Abstract: Serotonergic psychedelics are defined as compounds having serotonin 2A receptor (5-HT2AR) activation as an important pharmacological mechanism. These compounds include the phenylalkylamine class, containing substances with e.g. 2C-X structures (phenethylamines) or their N-methoxybenzyl analogues (NBOMes). Besides their abuse potential, psychedelics are increasingly recognized for having therapeutic benefits. However, many psychedelics remain incompletely characterized, even concerning their structure–activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 26 publications
11
42
0
Order By: Relevance
“…These findings also fit well with recent pilot in vitro data demonstrating higher 5HT2A receptor activation by 2,4-than 3,4-dimethoxylated NBOMe and NBF derivatives 63,64 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings also fit well with recent pilot in vitro data demonstrating higher 5HT2A receptor activation by 2,4-than 3,4-dimethoxylated NBOMe and NBF derivatives 63,64 .…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, most of 3,4-dimethoxy derivatives were behaviorally and neurochemically inert, except for 34H-NBOMe(F), that was highly anxiolytic and hallucinogenic, albeit at concentrations significantly higher than its 2,4-dimethoxy isomer, 24H-NBOMe(F). These findings also fit well with recent pilot in vitro data demonstrating higher 5HT 2A receptor activation by 2,4- than 3,4-dimethoxylated NBOMe and NBF derivatives 63, 64 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Early research into structure-function indicated that methylation of ergotamines at the N 1 position enhances serotonin antagonism in the isolated rat uterus assay [ 66 ], while decreasing hallucinogenic potency predicted from a quantitative structure-activity relationship (QSAR) study [ 67 ]. N -methyl-2-[ 125 I]-iodo-lysergic acid diethylamide ([ 125 I]-MIL, 24 ) was developed as a presumably non-hallucinogenic ligand for the molecular imaging of serotonin receptors, whereby N - methylation of [ 125 I]-LSD ( 25 ) was intended to impart greater selectivity and sensitivity for 5HT 2 receptors [ 23 ].…”
Section: Ex Vivo/in Vitro Binding Studies With Hallucinogensmentioning
confidence: 99%
“…Binding assays against [ 3 H]-ketanserin/[ 3 H]-mesulergine, [ 3 H]-LSD and [ 3 H]-Cimbi-36 in vitro showed that 25CN-NBOH ( 13 , N -(2-hydroxybenzyl)-2,5-dimethoxy-4-cyanophenylethylamine) had >52-fold K i 2C / K i 2A selectivity ratio and a 37-fold K i 2B / K i 2A ratio, and likewise showed substantial 5HT 2A selectivity in functional assays of IP turnover. Various isomers of 25H-NBOMe in which the two methoxy-groups are in different positions (ortho, meta, and para) were compared with respect to their efficacy in activating signaling pathways, in conjunction with molecular docking studies at the 5HT 2A receptor binding pocket [ 66 ]. In the series examined, several dimethoxy compounds proved to have an efficacy exceeding that of LSD ( 1 ).…”
Section: Ex Vivo/in Vitro Binding Studies With Hallucinogensmentioning
confidence: 99%